Novel Activity of a Synthetic Decapeptide Against Toxoplasma gondii Tachyzoites - Giovati, Laura; Santinoli, Claudia; Mangia, Carlo; Vismarra, Alice; Belletti, Silvana; D’Adda, Tiziana; Fumarola, Claudia; Ciociola, Tecla; Bacci, Cristina; Magliani, Walter; Polonelli, Luciano; Conti, Stefania; et al. (Frontiers in Microbiology, 2018)
The killer peptide KP is a synthetic decapeptide derived from the sequence of the variable region of a recombinant yeast killer toxin-like microbicidal single-chain antibody. KP proved to exert significant activities against diverse microbial and viral pathogens through different mechanisms of action, but little is known of its effect on apicomplexan protozoa. The aim of the present study was to evaluate the in vitro activity of KP against Toxoplasma gondii, a globally widespread protozoan parasite of great medical interest. The effect of KP treatment and its potential mechanism of action on T. gondii were evaluated by various methods, including light microscopy, quantitative PCR, flow cytometry, confocal microscopy, and transmission electron microscopy. In the presence of KP, the number of T. gondii tachyzoites able to invade Vero cells and the parasite intracellular proliferation were significantly reduced. Morphological observation and analysis of apoptotic markers suggested that KP is able to trigger an apoptosis-like cell death in T. gondii. Overall, our results indicate that KP could be a promising candidate for the development of new anti-Toxoplasma drugs with a novel mechanism of action.